A critical overview of the current myofascial pain literature – January 2020. Issue 2 (April 2020) - Dommerholt, Jan; Thorp, Jacob N.; Chou, Li-Wei; Hooks, Todd
Abstract: We are starting 2020 with 6 basic research studies, 9 review articles, 14 dry needling/injection studies, and one manual therapy paper for a total of 30 new papers. Topics range from studies on mechanisms, inflammatory mediators in myofascial pain, fascia, screening, Platelet-rich plasma intramuscular injections, and temporal summation to clinical studies on patients with tension-type headache, chronic pelvic pain, knee osteoarthritis, plantar fasciitis, generalized musculoskeletal pain, neck pain, breast cancer, tendinopathies, thoracic outlet syndrome, and canine dry needling, among others.